The Chasm Of Persistent Food Calorie Intake Defiency Of Proletarians In Nigeria's Northern States: A Perception Or A Reality? - sanusi mohammed sadiq; Ahmed Makarfi; Invinder Singh (Journal of Indonesian Applied Economics, 2022)
Food calorie deficiency due to poor purchasing power has been a nightmare affecting labour efficiency and productivity of the proletarians. The worsening state of the general price level with direct consequences on the purchasing power has relinquished the regional workforce to the ebb income class, thus facing-out the known middle-income class, a characteristic of this working class. Thus, based on this crux, this research was conducted to establish whether the chasm of the regional state civil servants retrogression into the trough-income category is real or a myth. A total of 375 sampled respondents were obtained through a multi-stage sampling procedure and valid data were sequestrated via structured questionnaires. Both descriptive and inferential statistics were used to analyze the data. It was established that a large chunk of the regional workforce fell below the recommended food security threshold level both energy and expenditure dimensions. Besides, an evidence of a significant and positive correlation was found to exist between the two-dimensions of food security. In addition, household size was observed to be the major driver of food security status in the studied area. Furthermore, it was established that the food security gap between the secured and unsecured owes to interaction effect in the case of calorie intake; and structural effect termed food security discrimination in the dimension of expenditure. Consequently, this is a clarion call on the policymakers to improve on the mechanisms that regulate the macroeconomic policies, especially the multiplier factor that drives inflation, thus containing the food insecurity plaguing its labour force. This intervention will not only be a plus for labour efficiency and productivity enhancement, but leverage for economic growth and development in both the region and the country in general.